Rnd3 regulates lung cancer cell proliferation through notch signaling. - Yongjun Tang; Chengping Hu; Huaping Yang; Liming Cao; Yuanyuan Li; Pengbo Deng; Li Huang (PLoS ONE, 2014)
Rnd3/RhoE is a small Rho GTPase involved in the regulation of different cell behaviors. Dysregulation of Rnd3 has been linked to tumorigenesis and metastasis. Lung cancers are the leading cause of cancer-related death in the West and around the world. The expression of Rnd3 and its ectopic role in non-small cell lung cancer (NSCLC) remain to be explored. Here, we reported that Rnd3 was down-regulated in three NSCLC cell lines: H358, H520 and A549. The down-regulation of Rnd3 led to hyper-activation of Rho Kinase and Notch signaling. The reintroduction of Rnd3 or selective inhibition of Notch signaling, but not Rho Kinase signaling, blocked the proliferation of H358 and H520 cells. Mechanistically, Notch intracellular domain (NICD) protein abundance in H358 cells was regulated by Rnd3-mediated NICD proteasome degradation. Rnd3 regulated H358 and H520 cell proliferation through a Notch1/NICD/Hes1 signaling axis independent of Rho Kinase.